2021
DOI: 10.1002/cbdv.202100079
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Biphenyl Derivatives from Sorbus pohuashanensis Leaves Infected by Alternaria tenuissi and Their Effect against Crop Pathogens

Abstract: Eight natural biphenyl‐type phytoalexins exhibiting antifungal effect were isolated from the leaves of Sorbus pohuashanensis, which invaded by Alternaria tenuissi, and their growth inhibition rate towards A. tenuissi were 50.3 %, 54.0 %, 66.4 %, 58.8 %, 48.5 %, 51.0 %, 33.3 %, and 37.0 %, respectively. In vivo activity assay verified the protective effect of these natural biphenyls on tobacco leaves. The observation of mycelial morphology revealed that these compounds possessed adverse effects on mycelial grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It has been reported in the literature that biphenyl derivatives exhibit a wide variety of biological properties, including anti-amoebic, antifungal, anti-infective, anti-hypercholesteremic, anti-hyperlipoproteinemic, antirheumatic, analgesic, anti-inflammatory, antithrombotic, uricosuric, and anti-arrhythmic properties [ 36 , 37 ]. For example, in our continuous efforts to develop new antimicrobials, we have found that some natural biphenyl-type phytoalexins, such as 3′,4′,5′-trimethoxy-[1,1′-biphenyl]-4-ol and 3,4,4′,5-tetramethoxy-1,1′-biphenyl, indeed showed significant activity against fungi [ 38 ]. However, research on their antibacterial activity against antibiotic-resistant bacteria is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in the literature that biphenyl derivatives exhibit a wide variety of biological properties, including anti-amoebic, antifungal, anti-infective, anti-hypercholesteremic, anti-hyperlipoproteinemic, antirheumatic, analgesic, anti-inflammatory, antithrombotic, uricosuric, and anti-arrhythmic properties [ 36 , 37 ]. For example, in our continuous efforts to develop new antimicrobials, we have found that some natural biphenyl-type phytoalexins, such as 3′,4′,5′-trimethoxy-[1,1′-biphenyl]-4-ol and 3,4,4′,5-tetramethoxy-1,1′-biphenyl, indeed showed significant activity against fungi [ 38 ]. However, research on their antibacterial activity against antibiotic-resistant bacteria is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that YE elicitation drastically increased biphenyl phytoalexin yield in Sorbus aucuparia (the same genus of SP) cell cultures, while other elicitors, such as Erwinia amylovora , Venturia inaequalis , and methyl jasmonate, did not show their effectiveness in the production of biphenyl phytoalexins [ 43 ]. In our previous studies, we also found that the effects of YE on biphenyl phytoalexin accumulation were more pronounced than other elicitors and these compounds showed evident antimicrobial activities against pathogenic fungi and drug-resistant bacteria [ 14 , 16 , 17 ]. That is why we selected YE as the elicitor in this work.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used as an herbal medicine for relieving cough, resolving phlegm, and strengthening the spleen, according to traditional Chinese medicine (TCM) theory [ 12 ], which contains a variety of chemical constituents, mostly terpenes, flavonoids, and organic acids [ 14 , 15 ]. Similar to other fruit trees, pathogen infection can cause huge economic damage to SP [ 16 ]. Sorbus pohuashanensis suspension cells (SPSCs) is a good and robust in vitro model for rapid accumulation and mechanism exploration of the secondary metabolites produced by plants under stress conditions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biphenyls are secondary metabolites regularly yielded especially from individual species of the Garcinia genus ( Chen et al, 2019 ). In addition, biphenyl can be classified as a phytoalexin that is produced in response to pathogen assault ( Zhou et al, 2016 ) and it can be extracted from a wide range of plants with related bioactive ability ( Teixeira et al, 2006 ; Yan et al, 2018 ; Ma et al, 2019 ; Yuan et al, 2019 ; Song et al, 2021 ). Because biphenyls have received little attention compared to PPAPs and xanthones in Clusiaceae, a comprehensive review of biphenyl chemicals in Clusiaceae is currently unavailable.…”
Section: Introductionmentioning
confidence: 99%